“Conversación y evaluación de las almendras de macambo (theobroma bicolor) frito-saladas” - Martínez Mena, Epifanio (2003)
The present study is oriented to find the appropriate parameters far the fritting and salting of the macambo almonds ( Theobroma bicolor). lt is specie that adapts itself satisfactorily to the agro-climatic conditions of the San Martín regían. A gre~t part of the work was carried out in the facilities of the Laboratory far Analysis and Compositi.on of foods,. being developed in two phases: extraction of the almond itself and the obtaining of the fried salted almond as a finished product. The fried salted macambo followed the subsequently unitary operations: Raw materialSlicingClassificationFryingWashingDryingPealingSaltingPackingStorage The sensorial test on the deep-fry carried out by the semi trained judges, showed a product with good organoleptic characteristic referred to Color with a rating of 4.3; Aroma with of 4.0; and Crispy with a rating of 3.7 respectively. In the salted fried almonds, a test of sensorial evaluation was made to determine lhe appropriate salting; being the best to a concentration of 1 %. The quality of the obtained product was evaluated, at the O; 30; 45; and 60 days of storage; finding out that the index of Peroxide was O.O; the index of Acidity was of 0.52% and the iodine value was of 15.73; being the best packing the threelaminated. The monomolecdlar layer was of 2.13 g H20/100 g of dry product.